Omicron variants of SARS-CoV-2 and long COVID - Yang, Chengliang; Zhao, Hedi; Shannon, Casey P.; Tebbutt, Scott J. (Frontiers in Immunology, 2022)
Understanding the epidemiology of long COVID and emerging variants has significant public-health implications as physical interventions and restrictions that help limit viral spread are eased globally. Here, we provide rationales for the necessity of updating current vaccines to improve protection against omicron and emerging variants, as well as more research into understanding the epidemiology and mechanisms of long COVID.